2005
DOI: 10.1007/s00018-004-4317-3
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium in Alzheimer?s disease: are we still at a crossroad?

Abstract: Aluminium, an environmentally abundant non-redox trivalent cation has long been implicated in the pathogenesis of Alzheimer's disease (AD). However, the definite mechanism of aluminium toxicity in AD is not known. Evidence suggests that trace metal homeostasis plays a crucial role in the normal functioning of the brain, and any disturbance in it can exacerbate events associated with AD. The present paper reviews the scientific literature linking aluminium with AD. The focus is on aluminium levels in brain, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
151
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(157 citation statements)
references
References 143 publications
2
151
0
4
Order By: Relevance
“…28,29 Although it was mentioned that aluminum might play a role in the pathogenesis of Alzheimer's disease, 30,31 some recent investigations denied this relationship. 32,33 On the other hand, there are few reports about aluminum hypersensitivity.…”
Section: Biocompatibility Of Ti-nb-al Alloy Composing Elementsmentioning
confidence: 99%
“…28,29 Although it was mentioned that aluminum might play a role in the pathogenesis of Alzheimer's disease, 30,31 some recent investigations denied this relationship. 32,33 On the other hand, there are few reports about aluminum hypersensitivity.…”
Section: Biocompatibility Of Ti-nb-al Alloy Composing Elementsmentioning
confidence: 99%
“…Al is a possible contributing factor in Alzheimer's disease (Campbell, 2002). Evidence for the contribution of Al to Alzheimer's disease (AD) remains contradictory (Flaten, 2001;Gupta et al, 2005). However, epidemiological studies have indicated a link between Al in drinking water and AD and a variety of human and animal studies have implicated learning and memory deficits after Al exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The elemental aluminium does not occur in its pure state but is always combined with other elements such as chloride, hydroxide, silicate, sulphate and phosphate. The wide distribution of this element ensures the potential for causing human exposure and harm [6][7][8][9].Evidence for contribution of aluminium to Alzheimer's disease remains contradictory [10][11]. Epidemiological studies have indicated a link between aluminium in drinking water and Alzheimer's disease (AD) and a variety of human and animal studies have implicated learning and memory deficits after aluminium exposure [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%